1984
DOI: 10.1557/proc-32-287
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrolytic Decomposition of Owens-Illinois Resin Gr650, an Organosilicon Compound

Abstract: The pyrolytic conversion of an organosilsesquioxane (Owens-Illinois resin GR650) to SiO2 is characterized by ir spectroscopy, thermogravimetry and evolved gas analysis (line-of-sight mass spectroscopy). Scanning calorimetry, ramping at 10°C/min, on the as-received (room temperature annealed) resin indicates a glass transition temperature of 67°C which decreases to 58°C for an unrelaxed sample. The ir spectra have bands which can be assigned to Si-CH3 and Si-O-Si modes. For 30 minute isothermal anneals at tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This may be explained mainly with the presence of pendant, nonbinding methyl groups and of branched, ladder, as well as polyhedral, cagelike structures in PMSSQ, which lead to a reduced mass density. Bagley et al have shown by infrared spectroscopic measurements, that the methyl groups are not removed upon curing at 420 °C or below . The undesired pyrolitic transformation of PMSSQ into SiO 2 occurs at temperatures higher than 600 °C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This may be explained mainly with the presence of pendant, nonbinding methyl groups and of branched, ladder, as well as polyhedral, cagelike structures in PMSSQ, which lead to a reduced mass density. Bagley et al have shown by infrared spectroscopic measurements, that the methyl groups are not removed upon curing at 420 °C or below . The undesired pyrolitic transformation of PMSSQ into SiO 2 occurs at temperatures higher than 600 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Bagley et al have shown by infrared spectroscopic measurements, that the methyl groups are not removed upon curing at 420 °C or below. 7 The undesired pyrolitic transformation of PMSSQ into SiO 2 occurs at temperatures higher than 600 °C. The larger decrease of the film electron density in the case of the samples which initially contained some porogen (cf.…”
Section: Structure Of Templated Polyorganosilicate Thin Filmsmentioning
confidence: 99%
See 3 more Smart Citations